Mari Mulai Berwirausaha: Membangun Kemandirian Ekonomi Warga RT.03 RW.04 Kelurahan Sawah Baru, Ciputat, Tangerang Selatan: Let's Start Entrepreneurship: Building Economic Independence Residents of RT.03 RW.04 Sawah Baru Village, Ciputat, South Tangerang - Windarko, Windarko; Saleh, Mohamad Zein; Prasetio, Teguh; Febriyantoro, Mohamad Trio; Felicia, Felicia (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This research discusses entrepreneurship as an approach to strengthen the community's economy, especially in the small business sector. Through the Community Service Program with the topic “Let's Start Entrepreneurship: Building Citizens’ Economic Independence,” this research aims to improve the entrepreneurial literacy of residents of RT. 03 RW. 04 Sawah Baru Village, Ciputat. This program provides the basics of entrepreneurship, which include business planning, financial management, and access to alternative funding. The method applied in this program is through socialization, participatory training, and evaluation. Participants were involved in the process of developing business plans and financial management simulations during the training. The results of the evaluation showed an increase in participants' understanding of entrepreneurship as well as higher motivation to start a small business. Participants also managed to identify business opportunities that are in line with existing local potential. The sustainability of the program is expected to be achieved through further training and ongoing business assistance, so that it can become a relevant community empowerment model and have a positive impact on other communities in the future.